The influence of live streaming and endorsement on product purchasing decisions at shopee with paylater as a moderating variable: Study on Shopee and Paylater Users in Pasuruan Regency - Nafi’ah, Nafi’ah; Sugiharto, Bagus Hari (Indonesia Auditing Research Journal, 2024)
The number of internet users in Indonesia continues to increase from year to year, which has an impact on the digital transformation of e-commerce use, one of which is Shopee. Sellers now don't need to meet consumers face to face, but can do live streaming (live broadcasts), or can collaborate with famous influencers to attract consumers. The buy now pay later feature is also an attraction in itself to influence consumer purchasing decisions. However, if paylater is used excessively there will of course be risks such as payment failure. The aim of this research is to analyze the influence of Live streaming and Endorsements on Purchasing Decisions with Paylater as a Moderating Variabel. This type of research is quantitative research. The population in this study were residents of Pasuruan Regency. The sample in this research consisted of 100 samples, using a nonprobability sampling technique using a purposive sampling model. This research uses primary data, data collection techniques using questionnaires and processed using statistical tools, namely WarpPLS. Based on the research results, it shows that partially the independent variabel, namely Live Streaming (X1), has a positive and significant effect on Purchasing Decisions (Y). Endorsement (X2) has a positive and significant effect on Purchase Decisions (Y). Paylater (Z) cannot moderate the influence of Live streaming (X1) on Purchase Decisions (Y). Paylater (Z) cannot moderate the influence of Endorsement (X2) on Purchase Decisions (Y).